Influence of K2DAV and K3DAV Animation Media on Learning Motivation Reviewing from the Academic Ability of Students - Wulan Tricahyani; Slamet Santosa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine the effect of K2DAV and K3DAV animation media on learning motivation in terms of the academic abilities of students in class X MIPA SMA N 1 Sukoharjo. The focus of the biological material studied is the component material, interactions, and energy flow in the ecosystem. This research is a quasi-experimental study with a post-test-only non-equivalent group design. The population consists of 7 classes, and the sample is taken by simple random sampling of as many as three classes. Class X MIPA 1 is an experimental class with K2DAV media. Class X MIPA 3 as experimental class 2 with K3DAV media. Class X MIPA 6 as a control class. Data collection is done through documentation, questionnaires, and observations. The research instrument was a student learning motivation questionnaire and an observation sheet on implementing discovery learning syntax. The data analysis technique was carried out by testing prerequisites and testing hypotheses. The prerequisite test was carried out for normality, homogeneity, regression, and linearity. In contrast, the hypothesis test used the Anacova test. The study results explain that discovery learning combined with K2DAV and K3DAV media affects learning motivation in terms of academic ability, and academic ability affects learning motivation.